OPTIMALISASI PERAN GURU PAI DALAM IMPLEMENTASI PENDIDIKAN ANTI-BULLYING DI MI NEGERI 2 SITUBONDO - Mushleh, Noer Khalis (PREMIERE : Journal of Islamic Elementary Education, 2025)
This study aims to examine the role of Islamic Education (PAI) teachers in implementing anti-bullying education at MI Negeri 2 Situbondo. Bullying remains a significant issue in elementary education and requires a character-based approach integrated into the learning process. This study employed a descriptive qualitative method, using observation, in-depth interviews, and documentation as data collection techniques. The results reveal that PAI teachers fulfill roles as educators, mentors, role models, information providers, and supervisors in instilling anti-bullying values in students. Various methods were applied, such as social guidance, assertiveness training, educational games, and active supervision. Supporting factors include the school’s strong religious culture and leadership support, while challenges include limited instructional time and the lack of specialized training for teachers in handling bullying cases.These findings indicate that strengthening Islamic values through PAI instruction positively influences students’ character development and contributes to a safer, more inclusive school environment. The integration of moral education with religious instruction enables students to build empathy, tolerance, and mutual respect. Therefore, continuous professional development and collaborative efforts among schools, teachers, and communities are essential to improve the effectiveness of anti-bullying initiatives.